Dog bites to children in the Czech Republic: the risk situations - Náhlík, Jan; Baranyiová, Eva; Tyrlík, Mojmír (Acta veterinaria Brno, 2010)
The aim of this study was to analyse dog bites to children in the Czech Republic. Data were obtained from a questionnaire completed with children aged 4 to 13 years in 11 urban and rural primary schools. A total of 103 dog bites sustained by 92 children were analysed using chi square test and F test. There were 58 boys (56.3%) and 45 girls (43.7%) bitten, 57.3% of them once, 42.7% repeatedly. The evaluated answers showed that children were bitten when playing with own dogs (69.2%) or dogs known to them (30.8%) but not by unknown dogs (χ2 = 25.397, df = 1, p < 0.001). Children were bitten outdoors by loose running unknown dogs (88.5%), known dogs (11.5%) but not by own dogs (χ2 = 55.528, df = 2, p < 0.001). Thirty-two children were bitten indoors by small (53.1%), medium size (21.9) or large (25.0%) dogs. Small dogs were biting mostly indoors (51.5%), medium size (73.1%) and large (80.5%) dogs bit mostly outdoors (χ2 = 9.0022, df = 2, p = 0.011). Most of the children that disturbed a resting or sleeping dog were bitten indoors (83.3%; χ2 = 7.862, df = 1, p < 0.01), predominantly by small dogs (83.3%, χ2 = 7.482, df = 2, p = 0.022). When stroking a dog, children were bitten by a medium size (45.5%), large (31.8%) or small dog (22.7%; χ2 = 5.588, df = 2, p < 0.068). Children injured by their family-owned dog had accidentally caused pain to it before being bitten (83.3%; χ2 = 7.862, df = 1, p < 0.012). These children were always bitten by a small dog (χ2 = 7.482, df = 2, p = 0.022). Three children reported deliberately causing pain to a dog – these were all small dogs (100.0%; χ2 = 6.279, df = 2, p < 0.05). Children teasing dogs were bitten most frequently by a small dog (75.0%; χ2 = 6.98, df = 2, p < 0.032). Male dogs bit more frequently (66.7%) than females (33.3%; χ2 = 6.338, d.f. =1, p = 0.014). These data were the first ones obtained from the bitten children. They suggest that in interactions with own, known and small dogs, children were more daring. The personal space of dogs, their warning signals, and defence were underestimated, the resulting aggression was mostly of possessive, territorial and fear type. Additional suggestions are made to complete the information on preventive measures for parents, children and the public. Importantly, all information types should point out that the dog remains a predator despite its long domestication history and close co-existence with humans.
Keywords: Animals; velikost těla; Human-Animal Bond; průzkumy a dotazníky; Female; vliv prostředí; dítě; předškolní dítě; ženské pohlaví; Surveys and Questionnaires; Adolescent; lidé; Body Size; kousnutí a bodnutí; Dogs; Risk Factors; Sex Factors; agrese; Male; sexuální faktory; Czech Republic; pouto mezi člověkem a zvířetem; Child, Preschool; rizikové faktory; Bites and Stings; Aggression; Česká republika; Child; zvířata; mužské pohlaví; mladiství; psi; Humans